Transport research implementation: current issues and lessons learned from Europe and China - Giannopoulos, George A.; Li, Yidong (Frontiers in Future Transportation, 2024)
The implementation of the research results is seen as a crucial step in the development of innovation in the transport sector. Moving to such an implementation is not always easy or straightforward. It requires a suitable organizational framework both inside as well as outside research producing entities and a number of other facilitating factors that are usually found within an innovation ecosystem. The paper examines systematically the conditions and prevailing practices for transport research implementation in Europe (the EU) and China and draws useful insights as to the factors that influence such implementation, the incentives, and other facilitating provisions that the research funding organizations can take. It also analyses the current practice and lessons learned for research implementation on the road to innovation production in four major areas of transport research namely. Automated Mobility, Intelligent Railways, Shared and Micromobility applications, and Electromobility.